Non-invasive geophysical prediction of deep rock mass UCS in complex geological settings - Muhammad Hasan; Lijun Su; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2026)

When defence mechanisms fail: Multi-omics evidence of antioxidant system collapse in Thymallus grubii liver under acute temperature stress - Xinchi Shang; Xinghua Che; Kai Ma; Huaifa Chen; Lanlan Zhang; Huizhi Sun; Yanjun Li; Meiqi Xing; Wei Xu; Wenhua Wu; Yongquan Zhang (Marine Pollution Bulletin, 2026)

Spatial heterogeneity of rock mass degradation and landslide susceptibility in the fault damage zone, Northwestern Himalayas, Pakistan - Izhar Ahmed; Yanjun Shang; Xueliang Wang; Muhammad Hassan (Bulletin of Engineering Geology and the Environment, 2026)

Paleolandslides, paleoshorelines and lacustrine sediment deformation structures in the midstream Tashkurgan River, Chinese Pamir and implications on regional seismic risk - Liao Liye; Zeng Qingli; Du Linlin; Du Changhong; Chen Xuan; Shang Yanjun; Zhou Yuanze (Bulletin of Engineering Geology and the Environment, 2026)

Reliable enrichment monitoring and removal of CrO42− and S2− using multivalent W-doped Ag quantum-dot biomimetic nanozyme - Ruhui Shang; Yanjun Han; Huitian Zhi; Xujie Wang; Yingchao Yang; Xiao Zhu; Lei Hu; Zhengquan Yan (Analytica Chimica Acta, 2025)

Geniposide Improves Corticosterone-induced Toxicity in PC12 Cells through the NMDARs and BDNF Pathway - Qi Ma; Yu Ma; Shizhuo Sun; Lei Yang; Tian Shi; Boxi Zhang; Bo Shang; Ruiyuan Zhou; Jingyuan Liu; Jiao He; Jing Hu; Yanjun Cao (Cell Biochemistry and Biophysics, 2025)

Evaluation of the Diametrical Core Deformation Analysis (DCDA) and Fracture Surface Morphology for In-Situ Stress Estimation - Qingsen Meng; Yanjun Shang; Jianjun Chi; Shengwen Qi; Muhammad Hasan; Xuetao Yi (Rock Mechanics and Rock Engineering, 2025)

Proline improves the developmental competence of in vitro matured porcine oocytes by enhancing mitochondrial function - Yazhuo Cheng; Jiyong Shang; Xilong Jia; Yongda Zhao; Jing Liu; Yanjun Huan; Jinghe Tan; Mingju Sun (Theriogenology, 2025)

Comparative analysis of chromatin accessibility in porcine oocytes from follicles of different sizes - Yazhuo Cheng; Jingyu Li; Jiyong Shang; Xilong Jia; Yeling Bi; Jiaxu Gu; Nan Jiang; Yanjun Huan; Youwei Li; Mingju Sun (Research in Veterinary Science, 2025)

Estimation of Young’s modulus for rocks using a non-invasive CSAMT method - Muhammad Hasan; Yanjun Shang; Qingyun Di; Qingsen Meng (Bulletin of Engineering Geology and the Environment, 2024)

Circulating metabolomics revealed novel associations between multiple ambient air pollutants exposure and chronic obstructive pulmonary disease incidence: Evidence from a prospective cohort study - Liangle Yang; Yanjun Guo; Yuxin Yao; Yujia Xie; Shiyu Yang; Bingxin Shang; Xiaojie You; Haoxiang Liu; Jixuan Ma (Environmental Pollution, 2024)

Influence of stress-induced fabric changes on the strength of granites: an insight from the Kohistan and Ladakh Himalayas, Northern Pakistan - Izhar Ahmed; Yanjun Shang; Muhammad Basharat; Khan Zada; Basit Ali Khan (Bulletin of Engineering Geology and the Environment, 2024)

Estimation of rock core indices for development of underground infrastructure using non-invasive geophysical methods - Muhammad Hasan; Yanjun Shang; Shengwen Qi; Qingsen Meng (International Journal of Rock Mechanics and Mining Sciences, 2024)

Associations of polychlorinated biphenyls exposure, lifestyle, and genetic susceptibility with dyslipidemias: Evidence from a general Chinese population - Yuxin Yao; Min Zhou; Qiyou Tan; Ruyi Liang; Yanjun Guo; Dongming Wang; Bin Wang; Yujia Xie; Haoyu Yin; Shiyu Yang; Bingxin Shang; Xiaojie You; et al. (Journal of Hazardous Materials, 2024)

Geophysical estimation of 2D hydraulic conductivity for groundwater assessment in hard rock - Qiang Gao; Muhammad Hasan; Yanjun Shang; Shengwen Qi (Acta Geophysica, 2024)

Hierarchical porous Pt/Hβ catalyst with controllable acidity for efficient hydrogenation of naphthalene - Zhentao Liu; Enhua Wang; Jinlin Mei; Aocheng Wang; Yutong Zou; Chunya Wang; Hui Shang; Yanjun Gong; Aijun Duan; Chunming Xu; Xilong Wang (Chemical Engineering Journal, 2024)

Determination of rock quality designation (RQD) using a novel geophysical approach: a case study - Muhammad Hasan; Yanjun Shang; Xuetao Yi; Peng Shao; He Meng (Bulletin of Engineering Geology and the Environment, 2023)

Coordinated development of land multi-function space: An analytical framework for matching the supply of resources and environment with the use of land space for ecological protection, agricultural production and urban construction - Yanbo Qu; Yanjun Zhang; Shilei Wang; Ran Shang; Haining Zong; Lingyun Zhan (Journal of Geographical Sciences, 2023)

Scalable fabrication of efficient and recycling wood residue-derived sponge for crude oil adsorption - Ying Shang; Runan Gao; Yaoxing Wang; Xiaofei Dong; Xueqi Li; Jianfu Tang; Xuan Wang; Jiuqing Liu; Yanjun Xie; Jian Li; Wentao Gan (Journal of Hazardous Materials, 2023)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Evaluation of Engineering Rock Mass Quality via Integration Between Geophysical and Rock Mechanical Parameters - Muhammad Hasan; Yanjun Shang; Peng Shao; Xuetao Yi; He Meng (Rock Mechanics and Rock Engineering, 2022)

Site suitability for engineering-infrastructure (EI) development and groundwater exploitation using integrated geophysical approach in Guangdong, China - Muhammad Hasan; Yanjun Shang; Weijun Jin; Gulraiz Akhter (Bulletin of Engineering Geology and the Environment, 2022)

Joint geophysical prospecting for groundwater exploration in weathered terrains of South Guangdong, China - Muhammad Hasan; Yanjun Shang; Weijun Jin; Gulraiz Akhter (Environmental Monitoring and Assessment, 2021)

Predicting collapse depth of paleocaves in carbonate reservoirs - Bin Zhao; Guangyou Zhu; Yanjun Shang; Hui Zhang (Carbonates and Evaporites, 2021)

Estimation of hydraulic parameters in a hard rock aquifer using integrated surface geoelectrical method and pumping test data in southeast Guangdong, China - Muhammad Hasan; Yanjun Shang; Weijun Jin; Gulraiz Akhter (Geosciences Journal, 2021)

Delineation of contaminated aquifers using integrated geophysical methods in Northeast Punjab, Pakistan - Muhammad Hasan; Yanjun Shang; Gulraiz Akhter; Weijun Jin (Environmental Monitoring and Assessment, 2020)

Molecular epidemiology of enterovirus from children with herpangina or hand, foot, and mouth disease in Hangzhou, 2016 - Wei Li; Cixiu Li; Lifang Liu; Xia Liu; Shiqiang Shang; Haiyan Mao; Yanjun Zhang (Archives of Virology, 2019)

An engineering site suitability index (ESSI) for the evaluation of geological situations based on a multi-factor interaction matrix - Kun Li; Yanjun Shang; Wantong He; Daming Lin; Muhammad Hasan; Kaiyang Wang (Bulletin of Engineering Geology and the Environment, 2019)

Determination of the geometrical REV based on fracture connectivity: a case study of an underground excavation at the Songta dam site, China - Yanyan Li; Jianping Chen; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2018)

Modification of rock mass strength assessment methods and their application in geotechnical engineering - Daming Lin; Kaiyang Wang; Kun Li; Wantong He; Weixing Bao; Renmao Yuan; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2017)

Deformation and failure of a tunnel in the restraining bend of a strike–slip fault zone: an example from Hengshan Mountain, Shanxi Province, China - Daming Lin; Renmao Yuan; Yanjun Shang; Weixing Bao; Kaiyang Wang; Zhongjian Zhang; Kun Li; Wantong He (Bulletin of Engineering Geology and the Environment, 2017)

Connectivity of Three-Dimensional Fracture Networks: A Case Study from a Dam Site in Southwest China - Yanyan Li; Jianping Chen; Yanjun Shang (Rock Mechanics and Rock Engineering, 2017)

Tetramethylpyrazine Promotes Migration of Neural Precursor Cells via Activating the Phosphatidylinositol 3-Kinase Pathway - Xiangying Kong; Micun Zhong; Xiaohui Su; Qingxia Qin; Hongchang Su; Hongye Wan; Cuiling Liu; Jiajia Wu; Hongcai Shang; Yanjun Zhang; Na Lin (Molecular Neurobiology, 2016)

Complete genome sequence of a sapovirus from a child in Zhejiang, China - Xiaohong Zhou; Yi Sun; Xiaochun Shang; Jian Gao; Xueqin Zhao; Huiqun Shuai; Rui Zhang; Yanjun Zhang (Virus Genes, 2016)

Modifications to the GSI for granite in drilling - Daming Lin; Yan Sun; Wei Zhang; Renmao Yuan; Wantong He; Bo Wang; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2014)

Deposition rate and interaction of human-riverine from height increase and permanent function of an 1180 years weir in Southeast China - YanJun Shang; Hyeong-Dong Park; ZhiFa Yang; SiGuang Chen; DaMing Lin (Science China Earth Sciences, 2014)

Some large values of in-situ stress and related engineering geological problems in China - Yanjun Shang; Hyeong-Dong Park; Yongyue Shi; Guangxiang Yuan; Yuanchun Sun (Geosciences Journal, 2010)

From in situ stress and discontinuities to the strength of granites: comparison and case study - Yanjun Shang; Hyeong-Dong Park; Guangxiang Yuan; Yuanchun Sun; Qian Gao (Geosciences Journal, 2008)

Flexible design of a rock slope abutment at the Wuqiangxi Hydroelectric Power Station - Yanjun Shang; Hyeong-Dong Park; Zhifa Yang; Da’an Liu; Chunhua Tang (Bulletin of Engineering Geology and the Environment, 2006)

Engineering geological zonation using interaction matrix of geological factors: An example from one section of Sichuan-Tibet Highway - Yanjun Shang; Hyeong-Dong Park; Zhifa Yang (Geosciences Journal, 2005)